Features of the Distribution and Placement of objects of Cognitive Tourism in Kuban and their Relationship - Kazachinskii, Vladimir P.; Stepanovskaya, Galina V.; Khasheva, Zarema M.; Shulgatyi, Oleg L. (International Journal of Economics and Financial Issues, 2016)
The article made the differentiation of administrative regions and territories in accordance with their core functions into four recreation and tourist area and fifteen recreational and tourist zones that will purposefully develop cultural tourism in the region. A next group of recreational and tourist areas: The Caucasus and the Black Sea; North Caucasus; Gorno-Caucasus; Azov. Compiled by generalizing the scheme zoning and distribution diagram objects of cultural tourism for recreational and tourist areas, zones and groups that characterize the cultural tourism objects in absolute terms (pcs.) And relative terms (%). We proposed four specific groups of objects of cultural tourism. The first group included recreational and tourist area with the number of them more than 20 objects of cultural tourism; second - their number from 16 to 20; the third group - a number of objects of cultural tourism 10-12; in the fourth - less than 10 objects of cultural tourism. Generalizing characteristic of the object of cultural tourism Kuban creates the necessary basis for the understanding of the processes of cultural tourism in the region, the development of constructive theoretical and methodological development of its platform with regard to their use. Keywords: cognitive tourism, recreation and tourist zones, objects of cultural tourism, cultural and natural sites JEL Classifications: O14, Q26, Q57, Q58